Antifungal compounds, GC-MS analysis and toxicity assessment of methanolic extracts of Trichoderma species in an animal model - Mulatu, Afrasa; Megersa, Negussie; Tolcha, Teshome; Alemu, Tesfaye; Vetukuri, Ramesh R. (PLOS ONE, 2022)
Fungi of the genus Trichoderma have been marketed for the management of diseases of crops. However, some Trichoderma species may produce toxic secondary metabolites and it should receive due attention to ensure human safety. In this study, we investigated the in vitro antagonistic potential of T. asperellum AU131 and T. longibrachiatum AU158 as microbial biocontrol agents (MBCAs) against Fusarium xylarioides and the associated antagonistic mechanism with bioactive substances. Swiss albino mice were used to evaluate the in vivo toxicity and pathogenicity of T. asperellum AU131 and T. longibrachiatum AU158 methanolic extracts and spore suspensions, respectively, in a preliminary safety assessment for use as biofungicides. Gas Chromatography-Mass Spectrometry (GC-MS) was used to profile volatile organic metabolites (VOCs) present in the methanolic extracts. The agar diffusion assay of the methanolic extracts from both T. asperellum AU131 and T. longibrachiatum AU158 were effective at a concentration of 200 μg/mL (1×107 spores/mL), causing 62.5%, and 74.3% inhibition, respectively. A GC-MS analysis of methanolic extracts from both bioagents identified 23 VOCs which classified as alcohols, acids, sesquiterpenes, ketones and aromatic compounds. The oral administration of methanolic extracts and spore suspensions of each Trichoderma species to female Swiss albino mice over 14 days did not show any significant signs of toxicity, mortality or changes to body weight. It can be concluded that the tested spore suspensions and methanolic extracts were not pathogenic or toxic, respectively, when administered to Swiss albino mice at various doses.